2015
DOI: 10.1016/j.jds.2015.02.001
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of missing-tooth effect on articular eminence inclination of temporomandibular joint

Abstract: Background/purpose: Occlusion is an important component of temporomandibular joint (TMJ). Little is known about the association between missing teeth and TMJ changes. The purpose of this study was to determine if a correlation exists between unilateral missing posterior teeth and changes in the inclination of the articular eminence (AE). Materials and methods: A total of 106 joints in 53 patients (20 men and 33 women) with unilateral posterior edentulism were included. In the same patients, the sagittal outlin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 18 publications
1
20
0
5
Order By: Relevance
“…When the patient is positioned correctly within the device, the bone components of the TMJ are clearly visible in the lateral oblique plane. 9,15 Tronje et al 24 in the AE's structure with age. 17,18 Gilboa et al 19 showed that there was a correlation between articular morphology and panoramic radiographic images, and the sagittal inclination of the articular eminence was consistently replicated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…When the patient is positioned correctly within the device, the bone components of the TMJ are clearly visible in the lateral oblique plane. 9,15 Tronje et al 24 in the AE's structure with age. 17,18 Gilboa et al 19 showed that there was a correlation between articular morphology and panoramic radiographic images, and the sagittal inclination of the articular eminence was consistently replicated.…”
Section: Discussionmentioning
confidence: 99%
“…[20][21][22][23] There are some studies that used panoramic radiography for measurement of the AEI. 9,15 Tronje et al 24 stated that angular measurements can be performed on correctly exposed panoramic films, and the values obtained Angle 27 and Wu et al 28 reported that the AEI increases with age, and other studies have reported an increase in morphological changes in the AE's structure with age. These studies also reported that this increase in morphological changes resulted in the flattening of eminence in the long term.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Hinton 9 described a decreasing depth of the glenoid fossa and flattening of the articular eminence in skulls with lost molars as compared to those with retained molars of the same 'functional age', determined by the extent of tooth wear. Chiang et al 10 examined patients with unilateral posterior edentulism and found a trend towards decreased inclination angle on the missing side in comparison with the non-missing side and no association between either age or gender and articular eminence angulation. Moreover, Levartovsky et al 11 showed that reduced molar support is the key etiological factor of the morphological osseous changes of the mandibular condyles and that the influence of age on those changes is negligible.…”
Section: Discussionmentioning
confidence: 99%
“…The symmetry equality between the missing and the non-missing side joint was 1.89%. This value was higher (3%) in the female group with the average of 52 years old in the range of age between 23 to 84 years old [1]. Meanwhile, based on data survey of Riset Kesehatan Dasar (RisKesDas) in 2007 the dental care condition of dentures user in Indonesia was around 4,5% [2].…”
Section: Introductionmentioning
confidence: 99%